Has Anything Changed? An Analysis of Federal Custodial Litigation Cases Post Kingsley v. Hendrickson - Tartaro, Christine (The prison journal, 2023)
The Supreme Court set a standard of deliberate indifference for correctional conditions of confinement cases and have historically required proof of staff members’ state-of-mind. The Kingsley v. Hendrickson decision signaled a shift from that subjective requirement when the court applied a less onerous objective standard in a case involving excessive force against a pretrial detainee. The question is how the Federal Appeals Courts would interpret Kingsley? Our findings indicate that the 12 courts differ in their application of the objective and subjective standards for conditions of confinement cases, including those for suicides of pretrial detainees.